2022
DOI: 10.1038/s41419-021-04479-w
|View full text |Cite
|
Sign up to set email alerts
|

EGF-induced nuclear translocation of SHCBP1 promotes bladder cancer progression through inhibiting RACGAP1-mediated RAC1 inactivation

Abstract: Bladder cancer is a highly heterogeneous and aggressive malignancy with a poor prognosis. EGF/EGFR activation causes the detachment of SHC-binding protein 1 (SHCBP1) from SHC adapter protein 1 (SHC1), which subsequently translocates into the nucleus and promotes cancer development via multiple signaling pathways. However, the role of the EGF-SHCBP1 axis in bladder cancer progression remains unexplored. Herein, we report that SHCBP1 is upregulated in bladder cancer tissues and cells, with cytoplasmic or nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…A recent study has shown that the adaptor protein RacGAP1 inactivated GTP-bound Rac1 in bladder cancer, but the activation was inhibited by protein SHCBP1 (SHC-binding protein 1), which is a regulator of EGF (epidermal growth factor). Via this relay, SHCBP1 can inactivate Rac1 and promote bladder cancer progression [ 83 ]. The EGF/EGFR ligand/receptor couple is frequently overexpressed in bladder cancers, with squamous bladder cancers qualified as being EGFR-addicted [ 84 ].…”
Section: Rac1 In Bladder Cancermentioning
confidence: 99%
“…A recent study has shown that the adaptor protein RacGAP1 inactivated GTP-bound Rac1 in bladder cancer, but the activation was inhibited by protein SHCBP1 (SHC-binding protein 1), which is a regulator of EGF (epidermal growth factor). Via this relay, SHCBP1 can inactivate Rac1 and promote bladder cancer progression [ 83 ]. The EGF/EGFR ligand/receptor couple is frequently overexpressed in bladder cancers, with squamous bladder cancers qualified as being EGFR-addicted [ 84 ].…”
Section: Rac1 In Bladder Cancermentioning
confidence: 99%
“…The expression of SHCBP1 was associated with lymph node metastasis in glioma, and patients with over-expressed SHCBP1 had a poor prognosis [ 28 ]. Moreover, the knockout of SHCBP1 reduced the migration and invasion ability in EGF-induced bladder cancer cells [ 11 ]. In addition, SHCBP1 plays an important role in FGF, NF-κB, MAPK/ERK, PI3K/AKT, and TGF-β1/Smad signaling, as well as participating in T cell development and downstream transduction regulation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…SHCBP1 expression is highly expressed mainly in hyperplastic tissues and cells, suggesting that it is involved in physiological roles and pathological changes in the organism [ 9 ]. Emerging studies have demonstrated that SHCBP1 was up-regulated in several cancers, including breast [ 10 ], bladder [ 11 ], and gastric cancer [ 12 ]. Aberrant expression of SHCBP1 is involved in the occurrence, development, metastasis and prognosis of cancer, suggesting that SHCBP1 has potential value in terms of biomarkers and therapeutic targets [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…EGF/EGFR activation results in the separation of SHC-binding protein 1 (SHCBP1) from SHC adaptor protein 1 (SHC1), which then translocates to the nucleus and promotes cancer development via multiple signaling pathways. 172 Yin et al 173 identified the EGF-SHCBP1-RACGAP1-RAC1 axis, revealing that SHCBP1 is upregulated in the tissues and cells of BC. Following Ser273 phosphorylation, the released SHCBP1 responds to EGF stimulation by transferring it to the nucleus.…”
Section: Clinical Studies On Inhibitors Targeting Egfr In Bcmentioning
confidence: 99%
“…169,188 (ii) The identification of new therapeutic targets has lagged: most of the studies did not explore the upstream targets, mainly downstream of the classic TKI targets. 173,187 (iii) Trials on the anti-BC activities of smallmolecule natural drugs have stagnated in the preclinical stages. Most of the activity studies of small molecule natural drugs are limited to effects on conventional signaling pathways.…”
Section: Challenges Of Tkis and Potential Solutionsmentioning
confidence: 99%